'For your ears only!' Donald Sterling and backstage racism in sport. Issue 15 (7th December 2016) - Hylton, Kevin; Lawrence, Stefan
ABSTRACT: The purpose of this paper is to elucidate how racism manifests 'behind closed doors' in the backstage private domain. We do this with reference to recent high-profile controversies in the US and UK. In particular, we use the concepts of frontstage (public) and backstage (private) racism to unpack the extraordinary case in point of the ex-National Basketball Association franchise owner Donald Sterling. The paper concludes that though it is important for frontstage racism to be disrupted, activist scholars must be mindful of the lesser-known, and lesser-researched, clandestine backstage racism that, we argue, galvanizes more public manifestations. The Donald Sterling case is an example of how backstage racism functions and, potentially, how it can be resisted.